2020
DOI: 10.21608/bjas.2020.187209
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Modified Albumin as A Biomarker in Predicting Oxidative Stress in Patients With Acne Vulgaris

Abstract: Acne vulgaris is a cutaneous chronic inflammatory disorder with complex pathogenesis. The aim of this study was to evaluate the serum level of IMA in patients with AV to evaluate its role in AV pathogenesis and its possible relation with oxidative stress markers in the disease.This study was conducted as a case-control study and was conducted on 30 patients suffering from AV (Group A) and 18 apparently healthy individuals of matched age and sex as a control group (Group B). All studied subjects were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Gurel et al divided the patients into three groups (patients with mild, moderate, and severe acne) and observed that there were no significant differences regarding the serum IMA level [56]. These results are consistent with those obtained by Ebrahim et al [52].…”
Section: Oxidative Stress Markers Evaluated In Acne Patientssupporting
confidence: 79%
“…Gurel et al divided the patients into three groups (patients with mild, moderate, and severe acne) and observed that there were no significant differences regarding the serum IMA level [56]. These results are consistent with those obtained by Ebrahim et al [52].…”
Section: Oxidative Stress Markers Evaluated In Acne Patientssupporting
confidence: 79%
“…Regarding the role of IMA as a marker of acne severity, the results are not clear. It seems that IMA levels can be influenced by the body’s compensatory mechanisms [ 36 ]. In the case of hidradenitis suppurativa, the two available studies show contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inflammatory process contributes to the formation of acne lesions. elevated in AV patients, serum IMA levels can be considered as an independent predictor of AV susceptibility and function [37].…”
mentioning
confidence: 99%